2007
DOI: 10.1007/s10753-007-9037-z
|View full text |Cite
|
Sign up to set email alerts
|

Acute Immune and Non-Immune Inflammatory Response in Spontaneously Hypertensive Rats and Normotensive Rats. Role of Endogenous Nitric Oxide

Abstract: The development of the inflammatory response in SHR differs from that in NTR, depending on the nature of the inflammatory stimulus. Endogenous NO plays a clear role in carrageenan-induced inflamma-tion, but not in immunologically mediated inflammation in the analyzed period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…For example, behavioral hyperalgesia that develops following carrageenan injection is similar to that produced by CFA in that local proinflammatory mediators, such as bradykinin, and reactive oxygen species directly activate and sensitize nociceptors (Morris, 2003). However, although carrageenan causes an immune response demonstrable by an increase in leukocyte count, it is generally considered a non-immune inflammatory stimulus, whereas CFA is specifically used as an immunostimulatory inflammatory agent (Stein et al, 1988;Woolf et al, 1997;Holmdahl et al, 2001;Morris, 2003;Ferreira et al, 2007). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, behavioral hyperalgesia that develops following carrageenan injection is similar to that produced by CFA in that local proinflammatory mediators, such as bradykinin, and reactive oxygen species directly activate and sensitize nociceptors (Morris, 2003). However, although carrageenan causes an immune response demonstrable by an increase in leukocyte count, it is generally considered a non-immune inflammatory stimulus, whereas CFA is specifically used as an immunostimulatory inflammatory agent (Stein et al, 1988;Woolf et al, 1997;Holmdahl et al, 2001;Morris, 2003;Ferreira et al, 2007). …”
Section: Discussionmentioning
confidence: 99%
“…However, although carrageenan causes an immune response demonstrable by an increase in leukocyte count, it is generally considered a non-immune inflammatory stimulus, whereas CFA is specifically used as an immunostimulatory inflammatory agent (Stein et al, 1988;Woolf et al, 1997;Holmdahl et al, 2001;Morris, 2003;Ferreira et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…These results corroborate data from previous studies showing that in certain circumstances SHRs exhibits decreased inflammatory and immunological responses compared with NTRs. Ferreira et al [9] reported a decreased in the vascular permeability in SHRs during the initial active anaphylaxis phase compared with NTRs. Kwasniewski et al [8,16,17], also found different responses in SHRs after triggering an anaphylactic response (e.g., increase in vascular permeability, activation of mast cells, contraction of respiratory pathways) when compared to NTRs.…”
Section: Discussionmentioning
confidence: 97%
“…We have demonstrated that SHRs does not develop the classical signs of acute inflammation when the inflammatory stimulus used to induce the response is the immunological nature (active anaphylaxis) [9].…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation